2005
DOI: 10.1373/clinchem.2005.050328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l-Carnitine on Acetyl-CoA Content and Activity of Blood Platelets in Healthy and Diabetic Persons

Abstract: Background: Excessive blood platelet activity contributes to vascular complications in diabetic persons. Increased acetyl-CoA in platelets from diabetic persons has been suggested to be a cause of this hyperactivity. We therefore investigated whether L-carnitine, which up-regulates metabolism of acetyl-CoA in muscles and brain, may affect platelet function in healthy and diabetic individuals. Methods: We obtained platelets from healthy and diabetic persons and measured acetyl-CoA concentrations, malonyl dialde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Such an experimental design was justified by our previous data (10) showing that diabetes-evoked changes both in the activities of enzymes of acetyl-CoA metabolism and in acetyl-CoA level depend on the degree of chronic hyperglycemia and not on other factors specific for a particular type of diabetes (9,10,23). Also, this study revealed that all laboratory markers of the disease, as well as levels of ATP/ADP in platelets, were increased to a similar extent in both type 1 and 2 diabetic patients (Tables 1 and 2 and data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such an experimental design was justified by our previous data (10) showing that diabetes-evoked changes both in the activities of enzymes of acetyl-CoA metabolism and in acetyl-CoA level depend on the degree of chronic hyperglycemia and not on other factors specific for a particular type of diabetes (9,10,23). Also, this study revealed that all laboratory markers of the disease, as well as levels of ATP/ADP in platelets, were increased to a similar extent in both type 1 and 2 diabetic patients (Tables 1 and 2 and data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Increased glucose influx into megacariocytes in the course of sustained diabetic hyperglycemia is a likely cause of the increased activity of several enzymes involved in glycolytic, energy-producing, and fatty acid-synthesizing pathways, and it activates acetyl-CoA synthesis (9,10). Elevated levels of acetyl-CoA in the platelets of diabetic subjects correlate with increased synthesis of thromboxane A 2 /malonyl dialdehyde and lipid peroxidation as well as spontaneous and thrombin-, ADP-, or collagen-evoked aggregation (9,10).…”
mentioning
confidence: 99%
See 3 more Smart Citations